The theory of the Revolutionary War of the French army in dealing with the Algerian issue 1954-1962 ad - Tamma, Younes; Abbad, Youcef (Journal of Ecohumanism, 2025)
This paper aims to analyze the history of French colonial policy in Algeria. This concerns the French army’s theory of revolutionary warfare, both in its security and military aspects, in dealing with the Algerian issue. Our study focuses on the basic strategy of what is known in French circles as the "counter-revolutionary war," which requires attacking rebels within the population and against the population itself, at a time when the army had come to combine political and military power. Within a methodological framework based on descriptive historical research, the study concludes that the French authorities in Algeria chose to place their full weight on the military effort and the use of force, especially with the expansion of the revolution and the widespread participation of Algerians in the National Liberation Front and Army. The study also aims to demonstrate the active cooperation of the state, which militarized while simultaneously politicizing the military. This contributed to establishing the necessary structural framework for seizing control of the Algerian population.